2016
DOI: 10.1177/1479972316674393
|View full text |Cite
|
Sign up to set email alerts
|

Amino terminal pro brain natriuretic peptide predicts all-cause mortality in patients with chronic obstructive pulmonary disease: Systematic review and meta-analysis

Abstract: Natriuretic peptides (NPs) are a family of prognostic biomarkers in patients with heart failure (HF). HF is one of the most frequent comorbidities in patients with chronic obstructive pulmonary disease (COPD). However, the prognostic role of NP in COPD patients remains unclear. The aim of this meta-analysis was to evaluate the relation between NP and all-cause mortality in COPD patients. We performed a systematic review and meta-analysis of observational studies assessing prognostic implications of elevated NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 37 publications
(65 reference statements)
4
37
1
2
Order By: Relevance
“…A meta-analysis also found that elevated NT-proBNP levels were associated with both in-hospital mortality and long-term mortality in COPD patients. 17 In our study, we also found that CHF was an independent risk factor for inhospital mortality (RR, 4.78; 95% CI, 1.55-14.72; P=0.006). This was consistent with previous findings in which CHF was a significant and independent risk factor of all-cause mortality in COPD and had a significant impact on COPD course.…”
Section: Discussionsupporting
confidence: 74%
“…A meta-analysis also found that elevated NT-proBNP levels were associated with both in-hospital mortality and long-term mortality in COPD patients. 17 In our study, we also found that CHF was an independent risk factor for inhospital mortality (RR, 4.78; 95% CI, 1.55-14.72; P=0.006). This was consistent with previous findings in which CHF was a significant and independent risk factor of all-cause mortality in COPD and had a significant impact on COPD course.…”
Section: Discussionsupporting
confidence: 74%
“…The biomarkers reflect different pathogenic mechanisms (inflammation, infection, cardiac overload, and cardiac injury), aligning with the many precipitants of COPD "exacerbation", which include heart failure, acute coronary syndromes (ACS) and arrhythmia [8]. Troponin and BNP were independently correlated with mortality, as observed in previous studies and systematic reviews [9,10]. Copeptin also exhibited a similar association, while CRP and PCT did not predict survival.…”
supporting
confidence: 53%
“…All five biomarkers have been the subject of numerous prognostic studies, systematic reviews or meta-analyses in acute COPD exacerbation [9,10,21]. Biomarkers are invariably associated with adverse outcomes, the strength of association influenced by population, comorbidities, inclusion/exclusion criteria, follow-up period, outcome studied, and adjustment methods.…”
mentioning
confidence: 99%
“…For our two conditions, these include ejection fraction and FEV 1 , and markers, such as brain natriuretic peptide, that are associated with poorer outcomes. 76 Although some were significantly associated with the outcomes, our proxies of intensive therapy unit bed use (variably recorded in HES), bronchoscopy, oxygen support and ventilation are not likely to capture severity very well. This will have contributed to the modest discrimination of our models and could have led to some of the unexplained variation between hospitals in their outcome rates.…”
Section: Discussion Of Methods and Findingsmentioning
confidence: 91%